Expanding repertoires and imaginaries from the reflection of a non-hegemonic pedagogical approach to the Teaching of Visual Arts (Revista Apotheke, 2022)
There is an insistent approach of (re)production of discourses, visualities and hegemonic ideologies in textbooks and curricula offered or for the teaching of the arts, thus strengthening the exclusive and prejudiced imagination about two cultural products from other temporalities and regionalities, other than Euro - North American, and productions by women artists. Therefore, in this work we seek to reflect on the ways that enable the construction of an anti-racist, anti-sexist, decolonial, horizontalized artistic education, attentive to prejudices in relation to class, gender, race, ethnicity, within other diversities. broad and social change that gives a view of the world. We analyze the work of the artist Gê Viana as a pedagogical possibility that contributes to an education that strengthens his criticisms and his autonomy in the construction of a non-hegemonic identity and worldview. We consider, then, that the pedagogical approach is a political choice of the teachers, being able to trace or not, analyzes and reflections with the students about the contexts, intentions, (re)constructions contained in the images, in addition to creating possibilities for the expansion of the repertoire visual and imagery. In addition, the work of artist Gê Viana may be a possible way to work on questions of gender, race, history, among others, which are only slightly strengthened in the history of art and not in teaching.
Keywords: Teaching of Visual Arts; Decolonial Studies; Pedagogy of Visuality